Pendampingan Tahsinul Qur’an pada Jama’ah Perempuan di Masjid Raya Kebenaran Kota Padang Sumatera Barat - Vadhillah, Syukra (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This mentoring aims to improve the reading of the holy verses of the Qur'an for female congregants of the Great Mosque of Truth. The methods used are lecture, discussion and talaqqi methods. The talaqqi method is a method of learning the Qur'an directly, face to face in a circle, if one person reads the holy verses of the Qur'an then the others critically remind them. However, the process of reminding requires tajwid knowledge which has not been fully mastered by the female congregants of the Great Mosque of Truth. The results of this mentoring have shown quite satisfactory results, the congregants have been able to read the holy verses of the Qur'an well and correctly and with the right ibtida' waqf. Although there are still one or two people who do not meet these criteria. However, overall the female congregants have been able to read the holy verses of the Qur'an well and correctly.